Characteristics of patients with systemic sclerosis suffering from a lower limb amputation: Results of a French collaborative study. Issue 3 (October 2020) - Bertolino, Julien; Jouve, Elisabeth; Skopinski, Sophie; Agard, Christian; Achille, Aurélie; Thoreau, Benjamin; Diot, Elisabeth; Sanges, Sebastien; Berthier, Sabine; Chaigne, Benjamin; Régent, Alexis; Martin, Thierry; et al.
Objective: Systemic sclerosis mainly affects the microvascular network. However, macrovascular manifestations have been reported. We aimed to investigate the characteristics of systemic sclerosis patients with an amputation of a lower limb segment. Methods: We designed a retrospective, case–control, multicentric study on systemic sclerosis patients with amputation of a lower limb segment secondary to critical ischemia via the French Research Group on Systemic Sclerosis. For each case, a control (systemic sclerosis patient without lower limb symptom) was matched with sex, age (±5 years), and cutaneous subset of systemic sclerosis. Results: In total, 26 systemic sclerosis patients (mean age of 67.2 ± 10.9 years, 20 females, 21 limited cutaneous forms) with a lower limb amputation and 26 matched controls (mean age of 67.3 ± 11.2 years, 20 females, 22 limited cutaneous forms) were included. At the time of amputation, the mean disease duration was 12.8 (±8.6) years. In comparison to controls, systemic sclerosis patients with amputation had more digital ulcers (p = 0.048), history of digital ulcers (p = 0.026), and a higher prevalence of pulmonary arterial hypertension (p = 0.024). Systemic sclerosis patients with amputation were more often smokers (p = 0.008) and under corticosteroids (p = 0.015). In the multivariate model, pulmonary arterial hypertension, smoking status, and corticosteroids were independent markers associated with lower limb amputation in systemic sclerosis. In the follow-up, 10 patients (38.5%) had recurrent ischemia requiring a new limb amputation, and five patients (19.2%) had an amputation of the contralateral limb. Conclusion: This study identifies some markers associated with lower limb amputation in systemic sclerosis such as digital ulcers and pulmonary arterial hypertension and points out the high risk associated with tobacco consumption and corticosteroid use.